1997
DOI: 10.1056/nejm199712183372504
|View full text |Cite|
|
Sign up to set email alerts
|

Lamotrigine for Generalized Seizures Associated with the Lennox–Gastaut Syndrome

Abstract: Lamotrigine was an effective and well-tolerated treatment for seizures associated with the Lennox-Gastaut syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
238
0
25

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 358 publications
(268 citation statements)
references
References 25 publications
5
238
0
25
Order By: Relevance
“…19,20,25 We assumed that the efficacies of these comparators after 3 months of treatment followed the same trends found for clobazam treatment. Relative clobazam efficacy (i.e., mean reduction in drop seizures) was calculated for 12 months versus 3 months (64.1%/62.1% = 1.03), and for 24 months versus 3 months (52.4%/62.1% = 0.83).…”
Section: Model Structure and Inputsmentioning
confidence: 99%
See 2 more Smart Citations
“…19,20,25 We assumed that the efficacies of these comparators after 3 months of treatment followed the same trends found for clobazam treatment. Relative clobazam efficacy (i.e., mean reduction in drop seizures) was calculated for 12 months versus 3 months (64.1%/62.1% = 1.03), and for 24 months versus 3 months (52.4%/62.1% = 0.83).…”
Section: Model Structure and Inputsmentioning
confidence: 99%
“…[17][18][19][20] Medical costs were estimated in a retrospective cohort analysis of claims data from a large managed health care plan. 27 Plan participants who had International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) codes for epilepsy (≥ 2 claims) and developmental delay (≥ 1 claim) from January 1, 2007, to September 30, 2009, were identified as LGS patients and included in medical cost analyses.…”
Section: Estimated Costsmentioning
confidence: 99%
See 1 more Smart Citation
“…In uncontrolled studies,6, 7, 8, 9, 10, 11, 12 70% of patients were considered to be “responders,” defined as having at least a 50% reduction in seizure frequency compared with baseline. In the RCT, however, the proportion of responders in the group randomized to lamotrigine was only 33%, compared with 16% in the group randomized to placebo 13. Thus, the actual gain in responder rate associated with active treatment versus placebo was actually 17% (33% minus 16%).…”
Section: Uncontrolled Studiesmentioning
confidence: 91%
“…Nevertheless, clinical trials have shown some AEDs to be particularly effective in children with specific epileptic syndromes. For example, vigabatrin is effective in the treatment of infantile spasms, particularly in children with tuberous sclerosis (37)(38)(39), and felbamate and lamotrigine demonstrate efficacy in Lennox-Gastaut syndrome (40,41). As emphasized by Dr. Baram, the brain changes dramatically across the life spans.…”
Section: Introductionmentioning
confidence: 99%